Determination of iron in hair samples by slotted quartz tube-flame atomic absorption spectrometry after switchable solvent liquid phase extraction - Atsever, Nihan; Borahan, Tulay; Bakirdere, Emine Gulhan; Bakirdere, Sezgin (ELSEVIER, 2020)
In this study, a green switchable solvent based liquid phase extraction (SS-LPE) method was developed for the determination of iron in human hair matrix at very low concentrations. The switchable solvent was synthesized from N,N-Dimethlybenzylamide (DMBA) and ultrapure water with the addition of dry ice for protonation, and used as the extraction solvent. The optimum conditions obtained for 8.0 mL aqueous solution after univariate optimization were 1.5 mL of pH 4.0 buffer solution, 0.75 mL of 0.015 % ligand solution, 0.75 mL of switchable solvent, 45 s vortex period for complexation and extraction, 1.25 mL of 1.50 M NaOH and 30 s vortex period after the addition of NaOH. Under the optimum conditions, a 92-fold improvement was obtained in the detection power of the flame atomic absorption spectrometry (FAAS). The limit of detection (LOD) and limit of quantification (LOQ) values were found to be 2.6 and 8.6 mu g/L, respectively. Linear range of the developed method was between 11 and 75 mu g/L, with a correlation coefficient (R2) value of 0.9992. Accuracy and the applicability of the proposed method were verified by recovery studies and the results obtained for 15, 20, 30 and 40 mu g/L spiked concentrations were 113.3 +/- 4.9, 90.6 +/- 4.4, 102.8 +/- 8.2 and 98.1 +/- 7.5 %, respectively. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Iron; Switchable solvent; Liquid phase microextraction; Flame atomic absorption spectrometry; Human hair; WATER; MICROEXTRACTION; NICKEL; LEAD; PRECONCENTRATION; OPTIMIZATION; COBALT; COPPER; METHODOLOGY; COMPLEXES; Chemistry; Pharmacology & Pharmacy